A Review on Chicken Feather Flour Potential for Fish Feed - Andriani, Yuli; Pratama, Rusky Intan; Hanidah, In In (Torani Journal of Fisheries and Marine Science, 2024)
The escalating demand for chicken meat over the years has led to a corresponding increase in waste generation, particularly chicken feathers. While efforts such as making dusters and cocks have been undertaken to address this issue, they have yielded limited success in effectively managing chicken feather waste. Given the significant levels of nutrients, including protein and amino acids, present in this waste, it holds immense potential as a raw material for fish feed. However, the utilization of chicken feather waste remains relatively uncommon due to the challenging digestibility of its large crude protein structure, primarily composed of keratin protein. Thus, preprocessing is essential to degrade the keratin within chicken feathers, rendering it digestible for fish. This review aims to provide an overview of the potential utilization of chicken feather meal in aquaculture, particularly in fish feed formulations, by exploring its nutritional value and various processing methods to enhance the quality of this raw material.